2017
DOI: 10.11124/jbisrir-2016-002965
|View full text |Cite
|
Sign up to set email alerts
|

The impact of essential fatty acid, B vitamins, vitamin C, magnesium and zinc supplementation on stress levels in women: a systematic review

Abstract: EXECUTIVE SUMMARY Background Women juggling multiple roles in our complex society are increasingly experiencing psychological stress. Dietary supplementation to manage stress is widespread despite limited supporting evidence. A systematic review of the available literature was undertaken to investigate the efficacy of specific dietary supplements in managing female stress and anxiety. Objectives To identify the impact of essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 107 publications
0
13
0
2
Order By: Relevance
“…In postmenopausal women with vitamin D deficiency, isolated supplementation of vitamin D3 were associated with a reduction in the metabolic syndrome risk profile, but also with a lower risk of hypertriglyceridemia and hyperglycemia [135,136,137]. Recent studies focused on other micronutrients such as essential fatty acid, B vitamins, vitamin C, magnesium, and zinc to reducing stress and anxiety [138,139].…”
Section: Vitaminsmentioning
confidence: 99%
“…In postmenopausal women with vitamin D deficiency, isolated supplementation of vitamin D3 were associated with a reduction in the metabolic syndrome risk profile, but also with a lower risk of hypertriglyceridemia and hyperglycemia [135,136,137]. Recent studies focused on other micronutrients such as essential fatty acid, B vitamins, vitamin C, magnesium, and zinc to reducing stress and anxiety [138,139].…”
Section: Vitaminsmentioning
confidence: 99%
“…This effect was exerted through alleviating oxidative damage. Furthermore, recently performed a systematic review also showed that high-dose Vit C supplementation was effective in reducing anxiety as well as stress-induced blood pressure increase [ 191 ].…”
Section: Role Of Vitamin C In Psychiatric Disordersmentioning
confidence: 99%
“…Moreover, a high intake of saturated fatty acids seems to be associated with a lower level of brain derived neurotrophic factor (BDNF), neuroplasticity and cognitive ability [ 25 ], that are involved in the pathogenesis of depression [ 5 , 6 ]. However, results are not concordant, and some observational studies have highlighted a protective effect of low-moderate consumption of red meat [ 26 , 27 ], probably due to the high bio-availability of vitamin B12, folates and zinc [ 28 , 29 ]. Zinc stimulates the BDNF expression, promoting differentiation and plasticity; its deficiency, on the contrary, decreases neurogenesis and increases the risk of depressive symptoms development [ 30 ].…”
Section: Introductionmentioning
confidence: 99%